2019
DOI: 10.1001/jamafacial.2019.0715
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Nasal Soft-Tissue Envelope Thickness for Rhinoplasty

Abstract: IMPORTANCEPreoperative assessment of nasal soft-tissue envelope (STE) thickness is an important component of rhinoplasty that presently lacks validated tools.OBJECTIVE To measure and assess the distribution of nasal STE thickness in a large patient population and to determine if facial plastic surgery clinicians can predict nasal STE thickness based on visual examination of the nose. DESIGN, SETTING, AND PARTICIPANTSThis retrospective review and prospective assessment of 190 adult patients by 4 expert raters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Although visual analysis of the nasal base by experts could predict the improvement but we did measurements by ruler in millimeter to find out evident outcome data. 12 The comparison of visual and photographic nasal patterns in this study showed a restoration to normal, almost like contralateral side of nasal opening in all cases. This surgical technique achieved nasal ventilation in a balanced pattern and has decreased nasal resistance for the airflow through the treated nasal opening, then increased the capacity of upper airway passage.…”
Section: Discussionsupporting
confidence: 59%
“…Although visual analysis of the nasal base by experts could predict the improvement but we did measurements by ruler in millimeter to find out evident outcome data. 12 The comparison of visual and photographic nasal patterns in this study showed a restoration to normal, almost like contralateral side of nasal opening in all cases. This surgical technique achieved nasal ventilation in a balanced pattern and has decreased nasal resistance for the airflow through the treated nasal opening, then increased the capacity of upper airway passage.…”
Section: Discussionsupporting
confidence: 59%
“…As described by Dey et al, the nasal STE was thickest at the sellion (6.7 ± 1.7 mm), thinnest at the rhinion (2.1 ± 0.7 mm), and then became thicker again over the supratip (4.8 ± 1.0 mm) and nasal tip (3.1 ± 0.6 mm), and thinned over the columella (2.6 ± 0.4 mm). 10 For each subsite, nasal STE thickness follows a near-normal distribution with the majority of patients in a medium thickness range. The mean nasal STE thickness was calculated for each nose by averaging the thickness at each subsite.…”
Section: Resultsmentioning
confidence: 98%
“…High-resolution maxillofacial protocol CT scans with 1-mm slices were read by two neuroradiology fellows using a standardized protocol previously described by Dey et al 10 In-house radiology measurement annotation software (QREADS) was used to measure the nasal STE thickness at the following anatomic sites for each patient: sellion, rhinion, supratip including the interdomal fat pad, 13 nasal tip, and columella. Mean nasal STE thickness was calculated by averaging the five subsite measurements for each nose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations